Drug utilization study of antihypertensive drugs used in the treatment of second and third trimester of pregnancy in tertiary care hospital - Lahamate, Shrikant B.; Razvi, Syed U.; Baig, Mirza S.; Doifode, Sudhakar M. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Hypertensive disorders are major cause of the perinatal and maternal mortality and morbidity worldwide. Aim of study was to evaluate current trend of antihypertensive drugs and to assess frequency and distribution of antihypertensive drugs in pregnancy. Methods: A retrospective observational study was conducted in a tertiary care hospital for period of six months in collaboration with department of obstetrics and gynaecology. Patients data recorded in case report form and analysed to study prescription pattern and related information. Results: Total of 104 cases were enrolled in this study. Prescribed antihypertensive drugs in pregnancy were Labetalol, Nifedipine, MgSO4 and furosemide. Most commonly prescribed drug was labetalol. In this study, Gestational hypertension was most common diagnosis in hypertensive disorder. Majority of drug prescribed from category C and A. In present study, Single drug therapy was most commonly prescribed for hypertension in pregnancy was 64.42% whereas multiple drug therapy was 35.57%. Most common maternal complication was anaemia i.e. 54.05% followed by placental abruption in 24.3%. Neonatal outcome was low birth weight i.e.36% followed by preterm birth i.e.24%. Conclusions: Labetalol found to be most common prescribed drug. Single drug therapy prescription was high as compared to multiple drug therapy prescription in hypertensive disorders in pregnancy. Gestational hypertension was most common cause of hypertensive disorder. Anaemia was found to be most common maternal complication encountered in hypertensive disorders in pregnancy. Most common adverse neonatal outcome was low birth weight.